The 21st century webster's international encyclopedia the new illustrated reference guide - Trident press international; Drubbel Bart (Colombia Trident Press International, 2005)
A concise,general- subject encyclopedia with color and black and white illustrations,maps and charts
A-Z entries----Chemical elements---Periodic table of elements---Metric conversion table---Illustrated survey of world history---Info-spreads index
Includes Index
Keywords: Children's encyclopedias and dictionaries; Encyclopedias and dictionaries